Conversations of opportunity in diabetes care. (2nd April 2021) - Phillips, Anne
Abstract : Anne Phillips explores the ways in which diabetes consultations can be maximised to deliver the best effects for people living with diabetes and health professionals involved in their care Changes to diabetes care due to the COVID-19 pandemic have caused extra pressures for both people living with diabetes and the health professionals involved in their care. Virtual and remote consulting has caused many health professionals to experience stress and usual face-to-face conversations with people living with diabetes have changed in context, frequency and delivery. The nuances of non-verbal communication can be lost in virtual consultations, so it is vitally important that health professionals are aware of this and consider how to deliver consultation conversations to the best effect. It is imperative that every contact counts and every virtual and face-to-face consultation has meaning for the person living with diabetes to maximise the benefit for the individual and their circumstances.